Universo refletido: história social, identidade e cidadania na obra de Jorge Amado - Moura, Sandra Regina Andrade de (2016)
This versa dissertation about the work of Jorge Amado (1912-2001), which is taking as objects of studies Jubiabá (1935), Bay of All Saints: Street Guides and Mysteries (1945) and Tent of Miracles (1969) were motivational books of all the academic enterprise that aims to foster discussions about identity and citizenship involving blacks, mestizos and miscegenation, coming from the literary profiles, sociological, anthropological and scientific nature. Our choice is related to the need to highlight the popular dimension and fiction writer policy in dealing with disquieting Brazilian issues, especially in Bahia, under the gaze of the best-selling Brazilian fiction, during a crucial period in the history of our country, profiled in the twentieth century.